Colorectal Anal Distress Inventory 8 (CRADI-8) Scores in PFDI-20 In Women With OASIS Before and After Repair - Mulyana, Rifqi Rahman; Sukarsa, M. Rizkar Arev; Rinaldi, Andi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objectives: This research aims to assess and compare CRADI-8 scores in women with grade 3-4 OASIS before and after surgical repair. Methods: This cross-sectional study analyzed 37 OASIS patients at Hasan Sadikin Hospital, Bandung (January 2021-December 2023). CRADI-8 scores were measured pre- and post-surgery, with scores categorized by grade (0-4). The McNemar test was used for statistical analysis (p